2018
DOI: 10.1101/481879
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of biomarkers and pathways to identify novel therapeutic targets in Alzheimer’s disease: Insights from a systems biomedicine perspective

Abstract: M.A.M.). # These two authors have made an equal contribution and hold joint first authorship for this work. (M.A.M.).Abstract: Background and objectives: Alzheimer's disease (AD) is the progressive neurodegenerative disease characterized by dementia, but no peripheral biomarkers available yet that can detect the AD. This study aimed to identify systems biomarker signatures in the AD through integrative analyses. Materials and Methods: We used two microarray transcriptomics datasets of blood from AD patients to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…In the present work, we studied gene expression data of AD and IS patients in order to identify genes dysregulated in both diseases that may be candidate disease biomarkers and potential therapeutic targets. The candidate biomarker genes were explored in microarray and RNA-seq studies of AD and IS, an approach now commonly used to identify interactions between complex diseases [14,15,18,19,25,26]. Our analysis of these gene expressions patterns seen in AD and IS patients revealed numerous significant alterations, with expression profiles of 26 transcripts (22 unique genes) (termed “common DEGs”) that were found to be dysregulated in both transcriptomic datasets.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present work, we studied gene expression data of AD and IS patients in order to identify genes dysregulated in both diseases that may be candidate disease biomarkers and potential therapeutic targets. The candidate biomarker genes were explored in microarray and RNA-seq studies of AD and IS, an approach now commonly used to identify interactions between complex diseases [14,15,18,19,25,26]. Our analysis of these gene expressions patterns seen in AD and IS patients revealed numerous significant alterations, with expression profiles of 26 transcripts (22 unique genes) (termed “common DEGs”) that were found to be dysregulated in both transcriptomic datasets.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, both involve neurological damage, and it is possible that there are shared pathological mechanisms underlying both conditions [8,9,10]. Several studies have tried to identify genetic links between IS and AD, for example, by genome-wide association studies; these have identified common genetic elements, mainly single nucleotide polymorphisms in IS and AD that point to at least some shared element in their pathogenesis [10,11,12,13,14,15,16,17,18], but the significance of these is currently uncertain. Molecular components that are commonly dysregulated in both diseases is, to date, very limited in AD and IS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gene expression analysis using microarrays is a global and popular method to develop and refine the molecular determinants of human disorders that have proven to be a sensitive method. We used these technologies to analyze the gene expression profiles of Parkinson's disease (PD), Alzheimer's disease (AD), Lou Gehrig's disease (LGD), Epilepsy disease (ED) and Multiple Sclerosis disease (MSD) to find the effects of welding fumes on them [24,25]. To uniform the mRNA expression data of different platforms and to avoid the problems of experimental systems, we normalized the gene expression data (disease state or control data) by using the Z-score transformation (Z ij ) for each NDGD gene expression profile using…”
Section: Analysis Methodsmentioning
confidence: 99%
“…Association studies also revealed links between the INPP5K gene and autophagy (Zirin et al, 2015), Parkinson (Nazeri et al, 2015;Zhu et al, 2018;Liu et al, 2019) and Alzheimer diseases (Rahman et al, 2020).…”
Section: Inpp5k Association With Other Biological Processes and Humanmentioning
confidence: 97%